Strudents egress course of course of Pedagogy, Education Child proof: where and where they work? - Caroline Silva (Universidade Federal de Santa Catarina, 2003)
This article points that the inclusion of veteran students of the Course of Pedagogy of UFSC the labor market and contribute to the debate on the formation and identity of (a) education (a). This interest is justified because the current curriculum has undergone an overhaul in 1995, when the base became the common teaching of the initial grades of elementary school (1st to 4th series). In the last year is that students may choose the qualifications: Guidance Education, School Supervision, Special Education and Childhood Education (0 to 6 years). As a tool for data collection was a questionnaire prepared and sent to the graduates of the course and details of where they are working. The return of some questionnaires show that most professionals have experience in Child Rearing, but not all currently work in this area. The activity of these ex-students in other levels of education, especially in the initial series, the show that not all still working in the area in which they formed.